On melting of boron subnitride B₁₃N₂ under pressure - Solozhenko, V.L.; Mukhanov, V.A. (Сверхтвердые материалы, 2017)
Melting of rhombohedral boron subnitride B₁₃N₂has been studied in situ at pressures to 8 GPa using synchrotron X-ray diffraction and electrical resistivity measurements. It has been found that above 2.6 GPa B₁₃N₂melts incongruently, and the melting curve exhibits positive slope of 31(3) K/GPa that points to a lower density of the melt as compared to the solid phase. Плавлення ромбоедричного субнітриду бору B₁₃N₂було вивчено in situ при тисках до 8 ГПа методами дифракції синхротронного випромінювання та вимірювання електричного опору. Було встановлено, що вище 2,6 ГПа B₁₃N₂плавиться інконгруентно, і крива плавлення має позитивний нахил 31(3) K/ГПа, що свідчить про меншу щільність розплаву в порівнянні з твердою фазою. Плавление ромбоэдрического субнитрида бора B₁₃N₂было изучено in situ при давлениях до 8 ГПа методами дифракции синхротронного излучения и измерения электрического сопротивления. Было установлено, что выше 2,6 ГПа B₁₃N₂плавится инконгруэнтно, и кривая плавления имеет положительный наклон 31(3) K/ГПа, что свидетельствует о меньшей плотности расплава по сравнению с твердой фазой.